Teacher Learning towards Equitable Mathematics Classrooms: Reframing Problems of Practice - Yvette Solomon; Elisabeta Eriksen; Annette Hessen Bjerke (MDPI AG, 2023)
This study responds to the debate on understanding and evaluating teacher learning in professional development programmes, with particular reference to the development of equitable mathematics classrooms. Conducted in the context of a year-long PD mathematics programme for primary teachers in Norway, designed to disrupt teachers' assumptions about mathematics pedagogy and how it relates to students' mathematical thinking, this study takes teachers' entry goals as its point of departure. Sixteen teachers participated in interviews at the end of the course. Recognising the situated nature of the development of pedagogic judgement in our analysis of teachers' reflections on their learning, we report on the shift in their "problems of practice" towards actionable concerns about student inclusion. We argue that this shift underpins a fundamental change in their assumptions about teaching and learning and a critical stance towards their own professional practice, suggesting an important indicator of what constitutes sustainable professional development for critical mathematics education.